RETRACTED: Perkembangan Penulisan Ilmiah Berkaitan Sifat 20 Di Malaysia: Satu Sorotan - Abdullah, Mohd Azman; Engku Alwi, Engku Ahmad Zaki (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
RETRACTEDFollowing a rigorous, carefully concerns, and considered review of the article published in Borneo International Journal of Islamic Studies, Vol. 1(1), November 2018 to article entitled “Perkembangan Penulisan Ilmiah Berkaitan Sifat 20 Di Malaysia: Satu Sorotan